Passive dispersal of phytoseiids (Acarina: Phytoseiidae) in a vineyard agro-ecosystem in Northern Italy (Bollettino di zoologia agraria e bachicoltura, 2024)
In the years 2001-2002 some experiments were carried out in order to find out the role of passive air dispersal of Phytoseiids in two vineyards in Northern Italy. The migrant mites were captured using aerial traps and the vine and the plant species around the vineyards were sampled. Eight species were collected on spontaneous flora, with a prevalence of Euseius finlandicus (Oud.) and Phytoseius sp.. There were six species on the vine and the dominant one was Typhlodromus pyri Scheuten. The data has confinned the importance of aerial dispersal. All the species present in the wood, except one, were collected in the traps and seemed to have the same migratory propensity. In the experimental area this migration seemed effective only on short distances due to the lack of wind. Aerial dispersal has a very important role in the first phase of colonisation of the Phytoseiids from spontaneous flora to the vineyard. The factors that condition the establishment are equally relevant and must be looked for among the characteristics of the varieties, of the climate and of the cultivation. Further studies are necessary in order to find out what cultural practices can increase the number of migrating specimens and in order to single out the importance of the single factors that regnlate the establishment.
Keywords: Vine; Spontaneous flora; Northern Italy; Phytoseiidae; Aerial traps; Colonization; Aerial dispersal